THE DYNAMICS OF POLICY CHANGE AND AGILE GOVERNANCE: HOW INDONESIAN GOVERNMENT RESPONSE TO COVID-19 PANDEMIC - Murti, Anak Agung Gde Brahmantya; Ilman, Ghulam Maulana (Universitas Padjadjaran, 2024)
Indonesia and other countries must deal with the COVID-19 pandemic with limited information control amid uncertainty. Handling a pandemic that has become a crisis places great demands on the government to provide agile and dynamic policies. Variations of policies that the Indonesian government has issued raise doubts in the public sphere. The government changed several policies quickly and easily, giving the impression that they did not go through a thorough formulating process. It shows that the handling of COVID-19 requires a policy system that is quite complex due to the many interactions of various sectors. By using qualitative methods, this study attempts to discuss the dynamics of changing public policies by using the concept of incremental policy amid demands for agile governance implementation by looking at the cases of policies issued by the Indonesian government in response to COVID-19. The dynamic of the policy network will be explored further to dismantle the discussion of policies for handling COVID-19 in Indonesia. Therefore, the results of this research show the challenges in implementing agile principles simply by changing and adapting policies to empirical conditions. In its application, agile governance shows several dominant actors who gather resources and support, shape policy outcomes, and advance their interests.